Parametric study on heat transfer characteristics of waste heat recovery heat exchanger for automotive exhaust thermoelectric generator - Hyun Kim, Ki.; Suresh Patil, Mahesh; Hyeong Seo, Jae; Jung Kim, Chan; Soo Lee, Gee; Yeon Lee, Moo (International Journal of Engineering and Technology, 2018)
Background/Objectives: The parametric study on heat transfer characteristics of waste heat recovery heat exchanger was carried out by varying different geometry parameters to suggest optimum model for automotive exhaust thermoelectric generator.Methods/Statistical analysis: The numerical analysis method was applied to compare the heat transfer characteristics of various heat exchanger models. For numerical analysis, various models were created using computer aided drawing considering different fin arrangements and guide plates. Commercial code ANSYS 17.0 was used to analyze the heat transfer and fluid flow behavior of various models. Mesh independency was conducted to enhance the accuracy of the results.Findings: The thermal performance analysis of waste heat recovery heat exchanger was conducted considering pressure drop and heat flux at cooling side. As the fin spaces were increased, the heat flux at cooling side increased, but pressure drop also increased.Improvements/Applications: The developed geometry can be further optimized considering other geometry parameters and efficient system could be developed for power generation using waste heat with heat recovery exchanger and the present study provides detailed numerical analysis considering pressure drop and heat flux.Â